2016
DOI: 10.21608/jacb.2016.40784
|View full text |Cite
|
Sign up to set email alerts
|

Parental Genetic Distance Based on Molecular Markers and Its Relationship With Heterosis in Rice

Abstract: This study was conducted at the farm of Sakha Agriculture Research Station during 2011 and 2012 growing seasons using nine parents and 36 hybrid combinations to study the relationship between genetic distances of parental genotypes and heterosis. The genetic distance of parental genotypes was determined by using functional genes markers related to yield traits. The correlation between genetic distance of parental genotypes and heterosis values was detected by determining 36 hybrids performance. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The assessment of genetic variation between parental genotypes is absolutely essential for the effective use of heterosis breeding In our study, cluster analysis mentioned a significant difference in diversity between parental genotypes (Fig. 1), there may be a high potential for obtaining the best new combinations by crossing of the genotypes with the highest genetic distance (El-Refaee et al, 2016). The study found that water stress conditions had a significant effect on all attributes when compared to normal conditions (Table 1).…”
Section: Variation Analysismentioning
confidence: 61%
“…The assessment of genetic variation between parental genotypes is absolutely essential for the effective use of heterosis breeding In our study, cluster analysis mentioned a significant difference in diversity between parental genotypes (Fig. 1), there may be a high potential for obtaining the best new combinations by crossing of the genotypes with the highest genetic distance (El-Refaee et al, 2016). The study found that water stress conditions had a significant effect on all attributes when compared to normal conditions (Table 1).…”
Section: Variation Analysismentioning
confidence: 61%